2013
DOI: 10.1371/journal.pone.0082565
|View full text |Cite|
|
Sign up to set email alerts
|

Integration of miRNA and Protein Profiling Reveals Coordinated Neuroadaptations in the Alcohol-Dependent Mouse Brain

Abstract: The molecular mechanisms underlying alcohol dependence involve different neurochemical systems and are brain region-dependent. Chronic Intermittent Ethanol (CIE) procedure, combined with a Two-Bottle Choice voluntary drinking paradigm, represents one of the best available animal models for alcohol dependence and relapse drinking. MicroRNAs, master regulators of the cellular transcriptome and proteome, can regulate their targets in a cooperative, combinatorial fashion, ensuring fine tuning and control over a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 73 publications
1
31
0
Order By: Relevance
“…The role of immune-related genes in alcohol dependence is also supported by genetic association studies and transcriptome meta-analysis in peripheral human cells (Boukli et al, 2010), postmortem brains of alcoholics (Liu et al, 2006; Okvist et al, 2007; Ponomarev, Wang, Zhang, Harris, & Mayfield, 2012), drinking models in mice (Gorini, Nunez, & Mayfield, 2013; Gorini, Roberts, & Mayfield, 2013; Nunez et al, 2013; Osterndorff-Kahanek et al, 2013), and vapor models for alcohol dependence in mice (Gorini, Nunez, et al, 2013; Gorini, Roberts, et al, 2013). Many immune-associated genes that are differentially expressed in brains of ethanol-treated mice are also differentially expressed in brains of human alcoholics.…”
Section: Alcohol Consumption and Neuroimmune-related Gene Expressionmentioning
confidence: 96%
“…The role of immune-related genes in alcohol dependence is also supported by genetic association studies and transcriptome meta-analysis in peripheral human cells (Boukli et al, 2010), postmortem brains of alcoholics (Liu et al, 2006; Okvist et al, 2007; Ponomarev, Wang, Zhang, Harris, & Mayfield, 2012), drinking models in mice (Gorini, Nunez, & Mayfield, 2013; Gorini, Roberts, & Mayfield, 2013; Nunez et al, 2013; Osterndorff-Kahanek et al, 2013), and vapor models for alcohol dependence in mice (Gorini, Nunez, et al, 2013; Gorini, Roberts, et al, 2013). Many immune-associated genes that are differentially expressed in brains of ethanol-treated mice are also differentially expressed in brains of human alcoholics.…”
Section: Alcohol Consumption and Neuroimmune-related Gene Expressionmentioning
confidence: 96%
“…A few reports have recently focused on the coregulation of components of miRNA biosynthetic pathways and covariation in miRNAs and target gene networks, as a means to develop a cohesive model for adaptation to alcohol (Gorini, Nunez, & Mayfield, 2013;Mulligan et al, 2013). The work of Giorini and colleagues represents on interesting and recent attempt to capture the complex relationship between miRNA and target gene expression through evolution of the process of dependence in a mouse model.…”
Section: Mirnas As Mediators Of Ethanol Effects In Developing and Adumentioning
confidence: 99%
“…The authors showed that new networks of miRNAs and targeted genes emerged at every stage from initial consumption to the development of dependence. miR-140-3p was an interesting example of a miRNA that appeared to function as a node within a covarying network of miRNAs and mRNAs, during the transition from alcohol consumption to dependence (Gorini et al, 2013). The authors showed that this miRNA was downregulated in the cerebral cortex while being upregulated in the midbrain, suggesting that the same miRNA may be regulated in opposite directions, in a region-specific manner, while still supporting the same overall biology, i.e., the transition from consumption to dependence.…”
Section: Mirnas As Mediators Of Ethanol Effects In Developing and Adumentioning
confidence: 99%
“…Gorini, Nunez, and Mayfield analyzed the global expression profile of miRNAs in the cerebral cortex and midbrain of mice submitted to chronic intermittent alcohol, and found different levels of expression in the brain regions studied. These data demonstrate that the changes caused by alcohol in the brain tissue, as regards the expression profile of the evaluated miRNA region, is very important 21 . In another study, also by global analysis of expression profiling by microarray technique, Mantha and Singh analyzed the exposure to prenatal ethanol in adult mice and found 20 miRNAs differentially expressed, and subsequently validated the miR-302c.…”
Section: Discussionmentioning
confidence: 60%